Introducción Anancy - Guzmán-Arias, Luis Carlos (My University, 2019)
En este vídeo animado, la araña Anancy realiza una breve presentación personal y nos invita a acompañarla en un recorrido por el Caribe de Costa Rica para aprender sobre algunas facetas de la cultura afrocostarricense.

In this animated video, the spider Anancy makes a brief personal presentation and invites us to accompany her on a tour of the Caribbean of Costa Rica to learn about some facets of Afro-Costa Rican culture.
Keywords: Cultura afrocaribeña; Caribe costarricense; Araña; Playas; Historia; Afro-Caribbean culture; Spiders; Beaches; History; Anancy